Adult Education Development and the NAEP. Report of the All India Adult Education Conference (32nd, Amritsar, India, October 7-9, 1979). Series No. 134 - Indian Adult Education Association, New Delhi; Indian Adult Education Association, New Delhi ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
This publication contains the proceedings of a conference held to discuss adult education and the National Adult Education Programme (NAEP) in India. Four major addresses are included in the booklet, along with references to other speeches, group discussion reports, resolutions, and recommendations. Inaugurating the conference, Shri J.J. Kidwai said that educational institutions were best suited to play their fullest part in the NAEP. He said that the campaign against illiteracy should be part of the larger development effort in the field of agriculture, industry, health and hygiene, family planning, vocational training, social reform, and social amelioration; and he urged rural participation in the program. Welcoming the delegates, Shri Jagjit Singh said that for a multi-faced development of the community, education had to play a vital role. He said that not only were the three R's needed but many other subject knowledges as well. He said that lack of education was the root cause of superstition, dirt, disease, backwardness, and parochialism. In his presidential address, Dr. M.S. Adisehiah emphasized the necessity of forming an effective state-level adult education association in Punjab to promote adult education in the state. He said that NAEP was a part of world-wide movements and that adult education should become part of the everyday life of the common people. Finally, in a valedictory address, Smt. S. Muthu said that the process of national development had changed the concept of adult education, which was previously confined to literacy alone. Now overall human resource development was needed, and special efforts should be made for adult education for women. Reports were presented on five group discussion topics. The conference program is appended to the publication. (KC)
Availability: Indian Adult Education Association, 17-B, Indraprastha Marg, New Delhi, India-110002 ($2.00).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Education; Adult Programs; Economic Development; Educational Development; Educational Needs; Lifelong Learning; Literacy Education; National Programs; Program Development; Program Implementation; Rural Population; Womens Education; India; National Adult Education Programme (India); Collected Works, Proceedings; Opinion Papers